COPD exacerbations · 1: Epidemiology - Donaldson, G C (BMJ Group, 2006)
The epidemiology of exacerbations of chronic obstructive pulmonary disease (COPD) is reviewed with particular reference to the definition, frequency, time course, natural history and seasonality, and their relationship with decline in lung function, disease severity and mortality. The importance of distinguishing between recurrent and relapsed exacerbations is discussed.